Comparison of various types of biomedia in river water treatment using attached growth activated sludge process - Hayder G.; Sidek L.M.; Mohiyaden H.A.; Basri H.; Ming Fai C. (Taylor and Francis Ltd., 2023)
activated sludge; bioreactor; pollutant removal; river water; water quality; water treatment; Malaysia